Fisetin-induced cell death, apoptosis, and antimigratory effects in cholangiocarcinoma cells - Benjaporn Buranrat, Laddawan Senggunprai,, Auemduan Prawan,, Veerapol Kukongviriyapan, (Journal of Applied Pharmaceutical Science, 2025)
Fisetin is a plant flavonol that can be discovered in vegetables and fruits and it has been related to certain anticancer properties. It may prevent metastasis, reduce tumor cell proliferation, and stimulate apoptosis. Fisetin may inhibit cholangiocarcinoma (CCA) cell migration and proliferation; however, its exact actions are still less information. The aim of the current study was to examine the actions of fisetin on two types of CCA cells, KKU-100, and KKU-M452, in terms of their ability to proliferate, undergo apoptosis, and migrate. The fisetin effect on cell growth was determined using sulforhodamine B, colony-forming ability, and distribution of cell cycle method. The apoptotic induction was explored by acridine orange/ethidium bromide (AO/EB) staining assay. Migratory suppression was determined by Transwell migration and Wound healing assay. The mechanism of cell death and apoptosis was measured by reactive oxygen species (ROS) generation. Fisetin was significant in suppressing CCA cell viability and colony formation during the course of this experiment. Moreover, fisetin significantly potentiated the cisplatin-induced CCA cells death by determination with a combination index (CI). Additionally, it reduced the CCA cells growth through stimulating apoptosis, as seen by a reduction in the viable cell numbers and an increase in apoptotic cells. Fisetin also reduced the migration of cancer cells and demonstrated more pronounced effects on KKU-M452 cells, which are characterized by rapid migration, compared to KKU-100 cells which are characterized by slow migration. Moreover, fisetin prompted cell death and apoptosis in CCA cells by stimulating the generation of ROS in KKU-100 cells at a dosage of 50 μM. According to these results, fisetin efficiently restricts the growth of both CCA cell types by preventing cell proliferation, inducing apoptosis, and stopping migration which are accomplished by producing ROS. Therefore, fisetin could be considered as a promising therapeutic approach for targeting CCA cells.
Keywords: Cell cycle arrest, Cholangiocarcinoma, Fisetin, reactive oxygen species (ROS) production, migration